Outcome of Adolescents with Acute Lymphoblastic Leukemia Treated by Pediatrics versus Adults Protocols. (17th November 2014) - Ibrahim, Abeer; Ali, Amany; Mohammed, Mahmoud M.
Abstract : Objective. Several studies showed better outcome in adolescents and young adults with acute lymphoblastic leukemia (ALL) treated with pediatrics protocols than similarly aged patients treated with adults protocols, while other studies showed similar outcome of both protocols. We conducted this study to compare the outcome of our pediatrics and adults therapeutic protocols in treatment of adolescents ALL. Patients and Methods. We retrospectively reviewed files of 86 consecutive adolescent ALL patients aged 15–18 years who attended to outpatients clinic from January 2003 to January 2010. 32 out of 86 were treated with pediatrics adopted BFM 90 high risk protocol while 54 were treated with adults adopted BFM protocol. We analyzed the effect of different treatment protocols on achieving complete remission (CR), disease-free survival (DFS), and overall survival (OS). Results. The 2 patients groups have almost similar characteristics. The CR was significantly higher in pediatrics protocol 96% versus 89%( P = 0.001 ) . Despite the fact that the toxicity profiles were higher in pediatrics protocol, they were tolerable. Moreover, the pediatrics protocol resulted in superior outcome in EFS 67% versus 39% (P = 0.001 ), DFS 65% versus 41%( P = 0.000 ), and OS 67% versus 45%( P = 0.000 ) . Conclusion. Our study's findings recommend using intensified pediatrics inspired protocol to treat adolescents with acute lymphoblastic leukemia.